1 .
г) (2a -3b²)(4a² +6ab² +9b⁴ ) = (2a)³ - (3b²)³ =8a³ -27b⁶.
- - - - - -
2.
а) 9x² - 25 =(3x)² -(5)² =(3x -5)(3x +5) ;
б) -4a² +8a -4 = -4( a² -2a*1 +1²) = - 4(a-1)² || = -(2(a-1) )² ||
в) 8y³ -8x³ = 8(x³ - y³) =8(x - y) (x² + xy + y²) ;
г) 9(a+2)²- 4 =( 3(a+2) ²) - 2² =( 3(a+2) - 2 )( 3(a+2) +2)=(3a+4)(3a+8) ;
|| =9a² +36a +32 ||
или 9(a+2)²- 4 =9(a² +4a +4) -4 = 9a² +36a +32
д) (a - 1)³ + 8a⁶ = (a - 1)³ + (2a²)³ = (a -1 +2a²)*( (a-1)² - (a-1)*2a² + (2a²)²) =
( 2a² + a - 1)*( 4a⁴ - 2a³ + 3a² - 2a + 1 ) .
е) (а - b)²+ 2(a-b)(a+3) + (a+3)² = (a -b +a+3)² = (2a -b +3)² .
- - - - - - -
3. Решите уравнение (4x+1)² - (4x+3)(4x-3) = 6x -2
(4x)²+2*4x*1 +1² - ( (4x)²- 3² ) = 6x -2
(4x)² +8x + 1 - (4x)² + 9 = 6x -2
8x - 6x = -2 -1 - 9
2x = -12
x = - 6
- - - - - - -
4 . 4x² - 4xy + y² =(2x)² -2*(2x)y + y² = (2x+y)² ≥0
x²-2xy+y²-4y²=0
(x-y)² - (2y)² =0
(x-y-2y)(x-y+2y)=0
(x-3y)(x+y)=0
x-3y=0 x+y=0
x=3y x= -y
При x=3y:
(3y)²-3y*y-2*3y-3y=6
9y²-3y²-6y-3y=6
6y²-9y-6=0
2y²-3y-2=0
D=3²-4*2*(-2)=9+16=25
y₁=(3-5)/4=-0.5 x₁=3*(-0.5)=-1.5
y₂=(3+5)/4=2 x₂=3*2=6
При x=-y:
(-y)² - (-y)*y - 2*(-y) -3y=6
y²+y²+2y-3y-6=0
2y²-y-6=0
D=1-4*2*(-6)=1+48=49
y₁=(1-7)/4=-1.5 x₁=-(-1.5)=1.5
y₂=(1+7)/4=2 x₂=-2
ответ: (-2; 2); (-1.5; -0.5); (1.5; -1.5); (6; 2).